2004
DOI: 10.1111/j.1601-5223.1993.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Studies for Agronomic Characters in Segregating Families of Spring Oilseed Rape (Brassica Napus)

Abstract: Knowledge of the extent and type of relationship between agronomic characters in oilseed rape is of relevance to plant breeders, in order to avoid selecting against an agronomically important character while performing early generation selection of another character. Genetic and phenotypic correlations for ten agronomic characters were calculated across and within four summer oilseed rape crosses. From each cross 32 F3 families were tested in the first year and 12 F3 families in the second year. The genetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Further, MarjanovicJeromela et al (2008) reported a moderate, positive, significant correlation and Tuncturk and Ciftci (2007) reported a low positive, significant correlation between TSW and seed yield. In contrast Lee et al (1977), Richards and Thurling (1979), Lefort-Buson and Dattee (1985), Engqvist and Becker (1993) and Basalma (2008) found no significant correlation between these two traits.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Further, MarjanovicJeromela et al (2008) reported a moderate, positive, significant correlation and Tuncturk and Ciftci (2007) reported a low positive, significant correlation between TSW and seed yield. In contrast Lee et al (1977), Richards and Thurling (1979), Lefort-Buson and Dattee (1985), Engqvist and Becker (1993) and Basalma (2008) found no significant correlation between these two traits.…”
Section: Discussionmentioning
confidence: 83%
“…The most interesting trait to use as an indirect means of selecting for yield is the TSW. This character is a yield component and is easier to determine than yield and generally has a high heritability (Engqvist and Becker, 1993). Leiah and Al-Khateeb (2005) and Ivanovska et al (2007) reported a high, positive, significant, correlation between TSW and seed yield.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seed size of C. sativa is highly heritable (Marquard and Kuhlmann 1986;Vollmann et al 1996) and accessions with larger seed have been developed, but with a corresponding decline in oil content and seed yield (Vollmann et al 1996). However, in a similar study on spring oilseed rape Engqvist and Becker (1993) observed no correlations between yield and other characters consistent over years and crosses, and reported positive correlations between seed weight and oil content, and seed weight and yield, for some crosses. Furthermore, in our trials the accessions with the largest seed were not necessarily those with the lowest oil content.…”
Section: Discussionmentioning
confidence: 98%